Assessment of China – Nigeria Trade Relations (1990-2018) - Opusunju Michael Isaac; AKYUZ Murat; INIM E. Victor (Randwick International of Social Science Journal, 2020)
The study assessed China- Nigeria trade relations covering a period of 29 years from 1990 to 2018. The study adopted the ex-post facto research design and obtained data for export and import transactions from the Central Bank of Nigeria statistical bulletin. The study used T-test, charts, and tables to address the engagement of China-Nigeria trade relations. The study used Microsoft excel software package and statistical package for social sciences (SPSS) version 20 to analysis the data. The study found that Nigeria has not gained from trade relations with China from 1990 to 2018 and it is only China that benefited from trade relations with Nigeria from 1990 to 2018. The study recommended that the Nigerian Government should re-strategise its industrial sector to enable the country to manufacture industrial goods and manufactured consumable goods as well as medical equipment to export to China. They should try to discover what type of industrial goods that China does not well produce and should re-strategise to produce it with low labour and low capital. The Chinese Government should continue to import goods to Nigeria since they are the ones benefiting from trade relations in Nigeria from 1990 to 2018. They should also encourage the Nigerian government to produce and manufacture industrial goods so that they can face a little competitive with Nigeria in the future for improvement of their products.